Jaguar status, distribution and conservation in south-eastern South America - Thompson, Jeffrey James (2023)
The jaguar Panthera onca has experienced a significant reduction in its global distribution, particularly in south-eastern South America. This chapter conducts an extensive assessment of the jaguar's distribution, population status, and threats in this region, encompassing Argentina, Paraguay, Uruguay, southern and eastern Bolivia, and south-eastern Brazil. Spanning 8.3 million km², this area contains diverse ecosystems, including tropical forests, grasslands, and wetlands, making it of global conservation significance. To assess jaguar distribution and population size, we employed a comprehensive dataset, expert opinions, and ecological models, categorising jaguar population status into four classes: Extinct, Possibly Extinct, Possibly Extant, and Extant. We estimated that jaguars are extant in 20% of their historical range, with potential existence in an additional 14%, primarily located in fragmented habitat patches. The Pantanal, Northern Chaco, and Chiquitano together emerge as a population stronghold, while the Atlantic Forest, Caatinga, and Eastern Cerrado exhibit lower jaguar occurrence. Country-level assessments indicate that the jaguar is extinct in Uruguay and has decreased extensively in distribution in Argentina and Paraguay. Bolivia retains substantial jaguar populations, particularly in the Chaco, Chiquitano, and Pantanal regions. South-eastern Brazil, despite extensive historic range loss, harbours a significant jaguar population, especially in the Pantanal and Cerrado. Our study underscores the importance of evaluating under-researched regions like the Bolivian Andes, Chiquitano Forest, Humid Chaco, Caatinga, and the Cerrado. Additionally, it highlights the need for conservation efforts in the Pantanal, northern Chaco, and the Chiquitano for the jaguar’s conservation. Moreover, our findings emphasise the urgency to restore populations and connectivity in the Atlantic Forest, Caatinga, and southern Chaco. Conservation priorities are habitat preservation, the maintenance of prey availability and landscape connectivity, and the reduction of hunting to secure jaguar populations in south-eastern South America.